Designing of manifold system for LPG and industrial gas at FKKSA'S laboratory - Mohd Rizuwan, Abd Wahab (2010)
Currently,Universiti Malaysia Pahang has several laboratories which required Liquefied Petroleum Gas(LPG) and industrial gas to run the experiments and other work related to the use of these gases.The equipments which use LPG and industrial gas are required continuously supply of these gases.Therefore,the manifold system shall be install to ensure that the LPG and industrial gas can be supplied without interruption such as running out of the gas.The scope of research work is about the gas demand where gaseous used by various equipments at the lab and type of gas that use at FKKSA Laboratory and safety aspect based on DOSH, Malaysian standards and Suruhanjaya Tenaga Guidelines.Have several steps to reach the objective of this project such as estimation of load demand, calculation number of gas cylinder based on gas demand,network study to identify length of tube,study of suitable area to locate the gas manifold based on standards and code,assessment in term of safety at the gas manifold area,proposed the location and selection of material for the tubing system between gas manifold system and the equipment,design the layout using PDMS software and the last one is about safety analysis. Based on the calculation,the number of gas cylinder required is about 55 cylinders and this gas can use for long period time because the capacity of gas supplied is enough for all equipment at the FKKSA laboratory run without running out of gas.About the safety,several aspect should be considered such as LPG storage safety, safe handling of compressed gases, hazard,general precautions and manifold cylinder location.Then,the layout design of tubing system will show us the flow of gas and the parameters of tubing like the actual length of tube.As conclusion,manifold system is relevant to install at FKKSA laboratory because the running out of gas during run the equipment can be avoid and will not give the problem when run the experiment using the equipment related with the gas consumption.